Hybrid diffusive-displacive helium outgassing in Cu/Nb multilayer composites. (15th March 2021) - Gao, Rui; Jin, Miaomiao; Li, Qing-Jie; So, Kang Pyo; Zhang, Lifeng; Wang, Xianping; Fang, Qianfeng; Sun, Cheng; Shao, Lin; Li, Ju
Abstract: Gas generation degrades material properties in nuclear applications. The construction of self-assembled bubble channels was proposed to help release gas to the surface. In this study, thermal desorption spectroscopy, in-situ TEM heating and molecular dynamics simulations were carried out to assess the outgassing feasibility in helium-irradiated Cu/Nb multilayers with low structural damage. We found that the formation of outgassing networks has a hybrid diffusive-displacive nature, with diffusive bubble coalescence and crack-induced displacive fracture. The latter could destroy the integrity of the multilayer structure. This suggests that the outgassing strategy making use of self-assembled cavity networks should be carefully designed to avoid large-scale structural failure. Graphical abstract: Image, graphical abstract